Decoding The Future: When Quantum Encryption Goes Dark - Bansal, Shreya (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2024)
The ascent of quantum computing presents both opportunities and challenges in the realm of cybersecurity, particularly concerning the dark web—a clandestine space for criminal activities. While the power of quantum computers to break conventional encryption methods raises concerns about data breaches, quantum cryptography, rooted in the principles of quantum mechanics, offers a potential solution. It is essential to note that current quantum hardware limitations restrain algorithms like Shor's and Grover's from immediately threatening established cryptographic methods on the dark web. Law enforcement's capability to harness quantum computing for tracking and apprehending criminals highlights the potential benefits of this technology. However, ethical considerations and responsible use are paramount as the landscape of the dark web evolves. Global collaboration and strategic utilization of quantum technologies are encouraged to strengthen cybersecurity measures and ensure a resilient defense against emerging threats. This paper underscores the ongoing necessity for advancements in both quantum computing and cryptographic defenses to sustain online security in the face of evolving challenges.